Single Molecule Spectroscopy Using C‐WAVE: Measuring narrow spectral features over wide frequency ranges. Issue 5 (December 2016) - Utikal, Tobias; Hens, Korbinian; Waasem, Niklas
Abstract: The fluorescence excitation spectra of single organic molecules in a solid‐state crystal are measured at cryogenic temperatures. As a tunable laser light source, the optical parametric oscillator C‐WAVE is employed, since it exhibits promising features as a laser light source for spectroscopy applications, like a broad tuning range from 450 to 650 nm, a narrow line‐width < 1 MHz, and mode‐hopfree tuning over > 25 GHz. This report presents the experimental setup and measured spectra, and it discusses the applicability of C‐WAVE for high‐resolution spectroscopy.